A systematic review of mands for information. (5th June 2022) - Cengher, Mirela; Bowman, Matthew D.; Shawler, Lesley A.; Ceribo‐Singh, Meghan Sonja M.
Abstract: The purpose of this paper was to conduct a systematic review of studies on mands for information. We used a combination of keywords to search for articles through PsycINFO® and then conducted reference and citation searches for all articles that met our inclusion criteria. In total, we identified 32 studies with 35 experiments. The most commonly investigated autoclitic frames were where and who, and the least investigated were why and how . Over half of the studies included an evocative scenario that served as a test condition, but did not include a control condition; however, there was an overall increasing trend toward including both conditions starting in 2007. The authors of the published studies reported that participants received information, which led to other reinforcers. We make recommendations for clinical practice, as well as discuss directions for future research.